Economic behavior: analysis and prospects - Lyudmila Alekseevna Migranova; Vladimir Borisovich Toreev; Aziza Viktorovna Yarasheva (Economic and Social Changes: Facts, Trends, Forecast, 2014)
Efficient social policy should be based on the understanding of strategies which Russian families use for adaptation to a difficult economic situation in the country. This understanding is promoted by regular research into people’s consumer behaviour and by sociological surveys of savings strategies. Scientists are studying the investment behaviour of population. Consumer behaviour, savings behaviour and investment behaviour are the elements of economic behaviour of population. The integrated research into these components gives the greatest effect for enhancing the efficiency of social policy. The “Taganrog” Project is one of such integrated studies. This project has been implemented within forty years; its main purpose is to study various aspects of life of households in this southern city that used to be an industrial city